2019
DOI: 10.1111/jfd.12942
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation dynamics of WSSV in crayfish, Procambarus clarkii, and the host responses at different temperatures

Abstract: The replication profile of white spot syndrome virus (WSSV) in crayfish, Procambarus clarkii, at different water temperature was investigated in this study. The WSSV detections were negative at 15 ± 1°C, and the natural infection ratio increased at 19 ± 1°C (24.2% ± 2.25%), reached 100% at 25 ± 1°C and decreased at 30 ± 1°C (93.2% ± 3.37%). The WSSV genome copies number was much higher at 25 ± 1°C (≥5 × 106.45 ± 0.35/mg) than at 15 ± 1°C (≤5 × 101.13 ± 0.12/mg), 19 ± 1°C (≤5 × 102.74 ± 0.48/mg) and 32 ± 1°C (≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Reports have also indicated that the optimum water temperature for WSSV to infect P. clarkii is 27–28°C (Guan et al., 2003; Withyachumnarnkul et al., 2003), which is consistent with the water temperature in that region in the months from June to August. Other reports have shown that the optimum water temperature for WSSV to infect P. clarkii is 25–30°C (Jiang et al., 2019; Moser et al., 2012), but the onset time of “Black May” is at the end of April and the beginning of May, when the water temperature in the middle and lower reaches and ponds of the Yangtze River is 15–20°C, which is significantly lower than the optimal water temperature for WSSV. In this study, PcDV positivity in P. clarkii coincided with “Black May” for two consecutive years, 2018–2019.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Reports have also indicated that the optimum water temperature for WSSV to infect P. clarkii is 27–28°C (Guan et al., 2003; Withyachumnarnkul et al., 2003), which is consistent with the water temperature in that region in the months from June to August. Other reports have shown that the optimum water temperature for WSSV to infect P. clarkii is 25–30°C (Jiang et al., 2019; Moser et al., 2012), but the onset time of “Black May” is at the end of April and the beginning of May, when the water temperature in the middle and lower reaches and ponds of the Yangtze River is 15–20°C, which is significantly lower than the optimal water temperature for WSSV. In this study, PcDV positivity in P. clarkii coincided with “Black May” for two consecutive years, 2018–2019.…”
Section: Discussionmentioning
confidence: 91%
“…The progress of the disease is dramatic with a swift increase in death rates (Deng, Liu, & Tang 2019). To date, the pathogen responsible for the “Black May” disease in P. clarkii remains undefined, with existing research focusing mainly on the white spot syndrome virus (WSSV) (Huang et al, 2019; Jiang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyclonal mouse antibody raised against non-structural protein (NS1) of TiPV was prepared by ABclonal (Wuhan, China) and used as the primary antibody. IFA was performed according to the protocol described by Ma et al [ 37 ] with slight modifications. Uninfected tissues samples and TiPV infected tissue samples were taken as negative controls and positive controls, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All the tissues were homogenized in lysis buffer, and virus genomic DNA was extracted using DNA viral kits (Omega, Germany) according to the manufacturer’s instructions. Real-time PCR reactions and quantitative analyses were performed primarily based on the previously described methods [ 37 ]. The primers used in this study are shown in Table 1 (TiPV-Fq/Rq).…”
Section: Methodsmentioning
confidence: 99%